Preoperative Immunotherapy in Hepatocellular Carcinoma: Current State of the Art - Laschtowitz A; Roderburg C; Tacke F; Mohr R (Journal of Hepatocellular Carcinoma, 2023)
Alena Laschtowitz,1 Christoph Roderburg,2 Frank Tacke,1 Raphael Mohr1 1Department of Hepatology and Gastroenterology, Charité – Universitätsmedizin Berlin, Campus Virchow Klinikum (CVK) and Campus Charité Mitte (CCM), Berlin, Germany; 2Clinic for Gastroenterology, Hepatology and Infectious Diseases, University Hospital Düsseldorf, Düsseldorf, GermanyCorrespondence: Raphael Mohr, Department of Hepatology and Gastroenterology, Charité – Universitätsmedizin Berlin, Augustenburger Platz 1, Berlin, 13353, Germany, Email raphael.mohr@charite.deAbstract: Hepatocellular carcinoma (HCC) is a malignancy that requires multidisciplinary evaluation to develop individualized and tailored treatment concepts. While liver resection and transplantation represent the mainstay of curative treatment in patients with early-stage HCC, disease recurrence remains an important burden. Immune checkpoint inhibitors (ICI) have become standard of care in the palliative setting, achieving promising response rates with overall good tolerability. Accordingly, ICIs are being evaluated in (neo)adjuvant concepts in order to improve survival. Nevertheless, neoadjuvant therapies are not recommended by current guidelines as they have not been proven to improve the outcome in large Phase III trials yet. Especially in the context of liver transplantation (LT), perioperative ICI usage is in need of a particularly critical risk–benefit assessment, as the immunotherapy may significantly increase the risk of rejection. In this review, we summarize available data on ICI-based perioperative treatment strategies in HCC. We discuss current drawbacks and challenges of this treatment concept and specifically highlight the risk of allograft rejection when ICI are given in patients (subsequently) considered for liver transplantation.Keywords: hepatocellular carcinoma, immune oncology, checkpoint inhibitor, neoadjuvant